The Functions Of Derivational Suffixes In The Novel “The Little Prince” Written By Antonie De-Saint Exupery - Meilandari, Ni Made Vindy; Nugraha Putra, I G B Wahyu; Sulatra, I Komang (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study focused on analysing the functions and the process of derivational suffixes found in the novel The Little Prince written by Antonie De-Saint Exupery. This study used quantitative method to account the percentage of the functions of derivational suffixes using table and qualitative method to identify and to give clear explanation about the functions and the process of derivational suffixes using description that is related to the theories proposed by Lieber (2009) and McCarthy (2002) which is used to discuss the process of derivational suffixes. To describe the result of this research it used formal and informal method. The functions of derivational suffixes consists of three types, such as category-changing lexeme formation, meaning-changing lexeme formation, and both category meaning-changing lexeme formation.